ASSA13-13-1 Long-Term Results with Coenzyme Q10 as Adjunctive Therapy in Chronic Heart Failure. (29th April 2013) - Mortensen, Svend Aage; Kumar, Adarsh; Dolliner, Peter; Filipiak, Krzysztof J; Pella, Daniel; Alehagen, Urban; Steurer, Günther; Ping, Chew Soon; Littarru, Gian P; Rosenfeldt, Franklin
Abstract : Objective: Dysfunction of bioenergetics and energy starvation of the myocardium may be a dominant feature of heart failure and attention has been directed towards agents which may stabilise myocardial metabolism and maintain adequate energy stores. The myocardial tissue level of the essential redox component of the respiratory chain Coenzyme Q10 (CoQ10) has been found inversely related to the severity of heart failure. We investigated in a double-blind trial the effects of CoQ10 on patients symptoms, functional capacity and biomarker status (NT-proBNP) and the long-term outcome with morbidity and mortality. Methods: Patients in New York Heart Association Class III or IV heart failure who were receiving current pharmacologic therapy were randomly assigned in parallel groups to either CoQ10 100 mg three times daily versus placebo. The primary long-term endpoint was the time to first MACE (major adverse cardiovascular event) including unplanned hospitalisation due to worsening of heart failure, cardiovascular death, urgent cardiac transplantation and mechanical support, using a time to first event analysis. Results: A total of 420 patients – CoQ10 (N = 202), placebo (N = 218) - from 17 international centres were enrolled with a follow-up time of 2 years. The two groups were similar with respect to a range of baseline characteristics. After 3 months there was a trend with reduced NT-proBNP in the CoQ10 group. After 2 years there was a significant improvement of NYHA Class in the CoQ10 group (p = 0.047). The primary endpoint was reached by 29 patients in the CoQ10 group, as compared with 55 patients in the placebo group (14 percent vs. 25 percent; hazard ratio CoQ10 vs. placebo: 2.0 (95% CI: 1.3–3.2); P = 0.003) by intention to treat analysis. CoQ10 treated patients had significant lower cardiovascular mortality (p = 0.02) and lower occurrence of hospitalizations for heart failure (p = 0.05). All cause mortality was also lower in the CoQ10 group, 18 patients vs. 36 patients in the placebo-group (9 percent vs. 17 percent; hazard ratio CoQ10 vs. placebo: 2.1 (95% CI: 1.2–3.8); p = 0.01). There were fewer adverse events in the CoQ10 group compared to the placebo group (p = 0.073). Conclusions: Q-SYMBIO is the first double-blind clinical trial in chronic heart failure addressing whether CoQ10 supplementation might improve survival. The CoQ10 treated patients had reduced hospital admission rates for worsening heart failure and lower cardiovascular death both of which may reflect a significant improvement in cardiac function. CoQ10 treatment was safe with a reduced all cause mortality rate. CoQ10 supplementation should be considered as a part of the maintenance therapy of patients with chronic heart failure.